1053 Sleep Duration And Timing Associated With History Of Breast Prostate And Skin Cancer: Data From A Nationally-representative Sample. (27th May 2020) - Piro, B; Garland, S; Jean-Pierre, P; Gonzalez, B; Seixas, A; Muench, A; Killgore, W D; Wills, C C; Grandner, M A
Abstract: Introduction: Sleep disturbances are a common problem among cancer survivors. Also, cancer patients can have altered circadian rhythms and these changes can continue to affect the patient long after the conclusion of their treatment. This analysis aims to investigate how the sleep and wake times of cancer survivors differ from the rest of the population, depending on the type of cancer. Methods: Data from the 2015-2016 National Health and Nutrition Examination Survey were used. Population-weighted data on N=5, 581 individuals provided complete data. History of breast, prostate, and skin cancer (melanoma or other) was self-reported. Sleep duration was self-reported in half-hour increments, and typical bedtime and waketime was self-reported. Covariates included age, sex, and race/ethnicity. Weighted linear regressions with sleep duration, bedtime and waketime were examined, with each cancer type as predictor. Results: Prevalence was 1.7% for prostate cancer, 1.5% for breast cancer, 2.3% for non-melanoma skin cancer, and 0.8% for melanoma. In adjusted analyses, prostate cancer was associated with an additional 26.5 minutes of average total sleep (95%CI 2.2, 50.9, p=0.03), a 23.1 bedtime minutes earlier (95%CI -40.4, -5.8, p=0.009), and no difference in waketime. Breast cancer was associated with a bedtime that was 41.1 minutes later (95%CI 10.3, 72.0, p=0.009) and a waketime that was 48.7 minutes later (95%CI 12.5, 84.9, p=0.008), but no difference in sleep duration. No statistically significant effects were seen for either type of skin cancer, melanoma or non-melanoma. Conclusion: Prostate cancer was associated with an earlier bedtime and associated increased sleep time. Breast cancer, on the other hand, was associated with a phase delay of the sleep period but no change in sleep duration. Skin cancer was not associated with differences in sleep duration or timing. These findings may have implications for not only treatment of sleep problems in different types of cancer, but also possible circadian mechanisms. Support: Dr. Grandner is supported by R01MD011600